Student Character Buliding Reconstruction Junior High School in District Galesong Takalar Based Values National Culture - Handayani, Trisna; Soesilowati, Etty; Priyanto, Agustinus Sugeng (Universitas Negeri Semarang, 2018)
Students in the District Galesong Takalar not understand the cultural values ​​of the nation so that they do not correspond to the violation of norms that exist in society. The purpose of this study build social studies learning models based on cultural values ​​of the nation. The method used is the method mix types equental exsploratory strategy, data collection techniques by observation, documentation interviews, and questionnaires. Use of data analysis techniques, data reduction, data presentation, inferences and simple linear regression test. The focus of research about learning model IPS. The results showed that the factors affecting the formation of the character of students in the Public Junior High School 2 Galesong Takalar including family environment by 83.0%, 54.2% of the school environment, relationships 68.4% and 55.1% of social media while at Madrasah Aliyah Assalamiah Galesong influence of family environment of 88.2%, 79.0% of the school environment, relationships 43.6% and 73.7% of social media. This study recommends value clarification technique study model for shaping the character of students in social studies.